A cycloruthenated 2-phenylimidazole: chromogenic sensor for nitrite in acidic buffer and fluoride in CH3CN. (15th February 2023) - Li, Zhen; Wang, Yirong; Xu, Ce; Li, Xianghong; Zhang, Bingguang
Abstract : A cycloruthenated 2-phenylimidazole as a colorimetric sensor can detect fluoride in CH3 CN by a great red-shift in absorption. However, it demonstrated sensitivity and selectivity to nitrite rather than fluoride in acidic buffer. Abstract : A cyclometalated ruthenium complex (1 ) using 2-phenylimidazole as the C, N -ligand was successfully synthesized and used as a chromogenic sensor. The as-prepared sensor displayed a good absorption centered at 565 nm in the visible region. Due to strong hydrogen bonding, the complex demonstrated high sensitivity and selectivity to fluoride over other common anions in CH3 CN solution. A large red-shift from 565 to 618 nm accompanied by a solution color change from red to green was achieved. However, in CH3 CN/Britton-Robinson buffer (V/V = 1 : 9, pH 4.5), the competition with water resulted in no changes for fluoride. Only the presence of nitrite caused the absorption intensity between 400 and 600 nm to decrease remarkably with the solution color fading to yellow. This phenomenon could be attributed to the formation of ruthenium nitrosyl, which was then isolated and characterized by MS, FT-IR and NMR spectra. Therefore, complex 1 can be used as a chromogenic chemosensor to detect fluoride in CH3 CN and nitrite in an acidic aqueous system, respectively.